Identification Of Chemical Markers And Quality Assessment In Malaysian Stingless Bee Honey Using Chemometric Techniques - Manickavasagam, Ganapaty (2023)
Heterotrigona itama (H. itama) honey is stingless bee honey produced by stingless bee species of H. itama. For H. itama honey to be commercialised in local and international markets, the adherence of honey to the quality assessment parameters is vital. In this study, moisture content, ash content, electrical conductivity, pH, free acidity, total dissolved solids, and 5-hydroxymethylfurfural (5-HMF) content in H. itama honey collected from three different provinces (Pulau Pinang, Kedah, and Perak) were assessed during its fresh state and after six months at two different storage temperatures (4 and 30 °C) and the obtained values were compared with Malaysian and international standards. In addition to quality assessment parameters, total phenolic and flavonoid contents, and multi-element compositions also were investigated. Subsequently, a geographical discrimination study was carried out using data from the mentioned analysis incorporated with volatile organic compounds in honey using multivariate analysis. The quality assessment analysis during fresh condition revealed that moisture content, ash content, free acidity, and total dissolved solids of most samples failed to meet the requirement set by international standards. In terms of the Malaysian Standard, the ash content of all samples exceeded the limit. Besides, although toxic minor elements (Cd, Ni, and As) were present in some samples, the estimated daily/weekly intake of these multi-elements was still below tolerable daily/weekly intake.